Economic Integration, Wage Policies and Social Policies - Michael Pflüger (Institute for the Study of Labor (IZA), 2003)
This paper uses a two country trade and geography model of monopolistic competition to study the effects of wage policies and social policies on the location of industry. It is first shown that a union wage push in one of two otherwise identical countries induces a relocation of firms which increases with the level of economic integration as measured by trade costs. This 'traditional view' is then contrasted with a 'new economic geography view' in which one of the countries has historically emerged as the core. The agglomeration rent which accrues to the mobile factor gives unions and governments in the core scope to set higher wages and to choose more generous welfare policies than their counterparts in the periphery without having to encounter an exit of firms. The relationship between the maximum international union wage differential and the level of integration is shown to be bell-shaped.
Keywords: F21; R12; F16; F15; F22; F12; 330; integration; wages; industry location; agglomeration; monopolistic competition; Wirtschaftsintegration; Industriestandort; Standorttheorie; Lohnpolitik; Sozialpolitik; Standortwettbewerb; Neue ökonomische Geographie; Monopolistischer Wettbewerb; Theorie